Analisis Transparansi dan Akuntabilitas Penggunaan Dana BOS (Studi Kasus di SMP Negeri 31 Maluku Tengah) - Manuhutu, Tirza; Adriansyah, Adriansyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The School Operational Assistance Fund (BOS) is government assistance as an effort to provide quality and affordable education to all levels of society at no cost. To achieve this goal, schools as education providers and recipients of BOS funds must be able to use the principles of accountability and transparency in the management and accountability of financial reports. Using qualitative descriptive methods, research was conducted at SMP Negeri 31 Central Maluku with the aim of finding out how BOS funds are managed and the implementation of accountability and transparency in financial reporting. Data collection was carried out using interviews, observation and documentation methods, while data analysis used data reduction techniques, data presentation and drawing conclusions. The results of the research show that the management of BOS funds at SMP Negeri 31 Central Maluku has been going well, as shown by the involvement of the BOS Fund management team, teachers and school committees starting from the planning, implementation and accountability stages which are in accordance with the technical instructions for the use of funds. BOSS. The implementation of the principles of accountability and management of BOS funds at SMP Negeri 31 Central Maluku has gone well. Accountability is carried out every quarter, then reporting transparency is shown by an information board regarding the actual use of BOS funds.